2014
DOI: 10.1186/1476-0711-13-25
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal carriage of Staphylococcus aureus among imprisoned males from Brazil without exposure to healthcare: risk factors and molecular characterization

Abstract: BackgroundPrevious studies report high prevalence of Methicillin-resistant Staphylococcus aureus (MRSA) colonization among imprisoned populations. However, there are no data on that prevalence in Brazilian correctional institutions.FindingsWe tested 302 male prisoners for nasopharyngeal colonization with Staphylococcus aureus from February 2009 through April 2010. The overall isolation rate of S. aureus was 16.5% (50/302). Men who had sex with men, users of inhalatory drugs and those with previous lung or skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Similar results have been reported in other studies [34,35]. A low frequency of the PVL gene was also observed in other studies conducted in the region [22,35,36].…”
Section: Discussionsupporting
confidence: 92%
“…Similar results have been reported in other studies [34,35]. A low frequency of the PVL gene was also observed in other studies conducted in the region [22,35,36].…”
Section: Discussionsupporting
confidence: 92%
“…In Brazil, the country presenting the lowest CG-MRSA burden in SSTIs, MRSA nasal colonization rates in the general population, even in at-risk populations, have been low. 54 , 55 , 56 …”
Section: Discussionmentioning
confidence: 99%
“…This fact reinforces the importance of throat colonization, which could be a route of transmission within the population examined. Other studies involving individuals from the same city and region also found CC5-ST5-IV and CC8-ST8-IV, suggesting that these strains are prevalent in the region [57][58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%